(untitled) (Academia Journal of Medicine, 2026)
Aim: The aim of the present study was to evaluate the effectiveness of an interdisciplinary approach in the management of traumatic dental injuries and to assess the long-term functional and esthetic outcomes following treatment of traumatized anterior teeth. Method: A prospective clinical observational study was conducted on 60 patients aged between 8 and 25 years presenting with traumatic dental injuries involving maxillary anterior teeth. A total of 84 traumatized teeth were included in the study. Patients underwent comprehensive clinical and radiographic examination to determine the type and severity of injury. Based on the diagnosis, an interdisciplinary treatment approach involving restorative procedures, endodontic therapy, orthodontic repositioning, and replantation when required was implemented. Patients were followed clinically and radiographically at 3, 6, and 12 months to evaluate functional recovery, tooth vitality, esthetic outcome, and the presence of complications. Result: The most common type of traumatic dental injury observed was crown fracture (40.5%), followed by luxation injuries (25%), avulsion (15.5%), root fractures (11.9%), and crown-root fractures (7.1%). At the end of the 12-month follow-up period, 85.7% of the treated teeth demonstrated successful outcomes, including normal function, absence of pain, and satisfactory esthetic restoration. However, 14.3% of the cases showed complications, such as pulp necrosis, discoloration, or root resorption. Conclusion: The findings of this study indicate that an interdisciplinary treatment approach significantly improves the prognosis of traumatized teeth. Early diagnosis, appropriate treatment planning, and coordinated management among dental specialties contribute to successful functional rehabilitation and satisfactory esthetic outcomes. Regular follow-up is essential to monitor healing and detect possible complications following dental trauma.